The Impact of Strategic Leadership on Sustainable Competitive Advantage of Commercial Banks in Zimbabwe - Chishamba, Jealous (Acta Universitatis Danubius. Œconomica, 2024)
This study examines the impact of strategic leadership (SL) on sustainable competitive advantage (SCA) in Zimbabwe’s commercial banks. Banks’ long-term competitiveness is critical for financial intermediation, economic growth, and social development. However, recurrent bank failures underscore deficiencies in SL practices and the Central Bank’s criteria for assessing banking leaders’ competences. Research on SL offers fragmented insights and inconsistent findings regarding its influence on sustained competitiveness. Similarly, studies on SCA present varying measurement criteria. This study integrates these diverse perspectives by operationalizing SL through six constructs: strategic direction, core competencies, strategic controls, human and social capital, corporate culture, and ethics. SCA is evaluated using five constructs: financial performance persistence, cost leadership, responsiveness, innovation, and supply chain management. A quantitative design was employed to analyze SL (independent variable) and SCA (dependent variable) in 13 commercial banks, representing 80% of Zimbabwe’s banking sector market share. Data collection achieved a 76% response rate from 500 questionnaires distributed to strategic leaders. The validity and reliability of SL and SCA measures were confirmed, and the model’s fit was assessed using structural equation modeling (SEM). SL has a significant positive impact on SCA, with a path coefficient of 0.605 (p < 0.05) and a 95% confidence interval (0.369–0.839), confirming a robust positive relationship. This study provides a quantitative framework for assessing SL’s impact on SCA, offering practical insights for leadership development and strategic management in banks. It recommends integrating SL constructs into regulatory fitness and probity assessments to enhance sustained competitiveness and mitigate bank failures emanating from failed SL practices. This research addresses gaps in measuring SL and its influence on strategic outcomes, presenting a validated model to enhance SL effectiveness and competitive performance in banking institutions.